Complete mitochondrial DNA analysis of eastern Eurasian haplogroups rarely found in populations of northern Asia and eastern Europe. - Miroslava Derenko; Boris Malyarchuk; Galina Denisova; Maria Perkova; Urszula Rogalla; Tomasz Grzybowski; Elza Khusnutdinova; Irina Dambueva; Ilia Zakharov (PLoS ONE, 2012)
With the aim of uncovering all of the most basal variation in the northern Asian mitochondrial DNA (mtDNA) haplogroups, we have analyzed mtDNA control region and coding region sequence variation in 98 Altaian Kazakhs from southern Siberia and 149 Barghuts from Inner Mongolia, China. Both populations exhibit the prevalence of eastern Eurasian lineages accounting for 91.9% in Barghuts and 60.2% in Altaian Kazakhs. The strong affinity of Altaian Kazakhs and populations of northern and central Asia has been revealed, reflecting both influences of central Asian inhabitants and essential genetic interaction with the Altai region indigenous populations. Statistical analyses data demonstrate a close positioning of all Mongolic-speaking populations (Mongolians, Buryats, Khamnigans, Kalmyks as well as Barghuts studied here) and Turkic-speaking Sojots, thus suggesting their origin from a common maternal ancestral gene pool. In order to achieve a thorough coverage of DNA lineages revealed in the northern Asian matrilineal gene pool, we have completely sequenced the mtDNA of 55 samples representing haplogroups R11b, B4, B5, F2, M9, M10, M11, M13, N9a and R9c1, which were pinpointed from a massive collection (over 5000 individuals) of northern and eastern Asian, as well as European control region mtDNA sequences. Applying the newly updated mtDNA tree to the previously reported northern Asian and eastern Asian mtDNA data sets has resolved the status of the poorly classified mtDNA types and allowed us to obtain the coalescence age estimates of the nodes of interest using different calibrated rates. Our findings confirm our previous conclusion that northern Asian maternal gene pool consists of predominantly post-LGM components of eastern Asian ancestry, though some genetic lineages may have a pre-LGM/LGM origin.